Long-term effects of leaked oil vibration corrosion on the high-temperature performance of rubber asphalt and asphalt mixtures - Zheng, Xing; Fan, Aiming; Ran, Pan; Liao, Jianfeng; Guo, Peng; Lu, Tenglong (Frontiers in Materials, 2025)
Experiments were conducted on rubber asphalt (RA) corroded by leaked oil for different durations in order to study the long-term damage of leaked oil on the high-temperature performance of RA pavement. Asphalt physical property test, dynamic frequency scanning, temperature scanning, MSCR test, FT-IR, GPC test and TG test, were performed to investigate the influence of leaked oil on the high-temperature performance of rubber asphalt and rubber mixture. Based on the Grey Relation Analysis, the macro factors of asphalt that affect the high-temperature stability of asphalt mixtures were explored, and the correlation was analyzed between these macro factors and micro characteristic indicators. Physical experiments have shown that the complex shear modulus of rubber asphalt plunges after oil corrosion. The creep recovery rate(R) of rubber asphalt decreases after the oil corrosion, while the non-recoverable creep compliance (Jnr) significantly increases. Microscopic experiments revealed that oil corrosion lowers the mass loss temperature of rubber asphalt, with more severe corrosion causing greater temperature reduction. The chromatogram curves shift toward smaller molecules, reducing large molecule content while increasing small molecule components. Grey correlation analysis shows that MSCR test indexes (R and J) can predict permanent deformation of asphalt mixtures. This study provides a theoretical basis for enhancing the oil corrosion resistance of rubber asphalt pavements.